An Evaluation of Initial Vancomycin Dosing in Infants, Children, and Adolescents - Laura Broome; Tsz-Yin So (International Journal of Pediatrics)
Background. The pharmacokinetics of many medications change as we age, thus most would assume dosing strategies would adjust for these changes. The objective of this study is to evaluate the initial vancomycin dosing in three pediatric age groups based on measured serum trough concentrations. Methodology. This retrospective database review included patients aged from 1 month to 18 years old admitted to the Moses H. Cone Memorial Hospital. Patients had to have received vancomycin dosed at 15 mg/kg every 8 hours with an appropriately measured trough concentration. The primary outcome was to determine the percentage of patients in 3 pediatric age groups achieving therapeutic trough concentrations with the initial vancomycin dosing regimen. Results. Twenty-five patients were included in the study. None of the patients had therapeutic trough concentrations after receiving vancomycin 15 mg/kg every 8 hours. Only one patient had a supratherapeutic level, while all of the other patients had levels less than 10 mcg/mL. Conclusions. Vancomycin 15 mg/kg every 8 hours did not provide therapeutic serum trough concentrations for any pediatric age groups. Higher doses and/or more frequent dosing regimens need to be evaluated for each age group to determine the most appropriate strategies for producing therapeutic trough concentrations.